Knowledge graph completion for scholarly knowledge graph - Taufiqurrahman, Taufiqurrahman; Wiharja, Kemas Rahmat Saleh; Wulandari, Gia Septiana (Association for Scientific Computing Electrical and Engineering, 2024)
Scholarly knowledge graph is a knowledge graph that is used to represent knowledge contained in scientific publication documents. The information we can find in a scientific publication document is as follows: author, institution, name of journal/conference, and research topic. A knowledge graph that has been built is usually still not perfect. Some incomplete information may be found. To add the missing information, we can use knowledge graph completion, which is a method for finding missing or incorrect relationships to improve the quality of a knowledge graph. Knowledge graph completion can be carried out on a scholarly knowledge graph by adding new entities and relationships to produce further information in the scholarly knowledge graph. The data added to the scholarly knowledge graph are only other papers of first author entity, the research field of first author entity, and a description of the conference/journal entity. The result shows that the scholarly knowledge graph was completed by adding 81% correct data for other papers of first author entity, 80.3% correct data for the research field of first author entity, and 53.9% correct data for the description of the conference/journal.